Myth or reality? Some directions on translation universals in recent corpus based case studies - Jia, Juan; Afzaal, Muhammad; Naqvi, Swaleha Bano (Frontiers in Psychology, 2022)
This paper contributes to the ongoing debate on the existence of translation universals by mapping the theoretical literature on translation universals (TUs) and evaluating selected corpus based studies which explore a swath of hypothesized universals. Based on a review of empirical research over the past years in translation studies, this paper attempts to develop a holistic picture of the evidence on TUs pertaining to multiple aspects of translation. We found that while some evidence for certain hypothesized universals exists, claims cannot be made in favor of TUs being an indisputable reality. The findings of this study are relevant for translation studies as they show that cognitive abilities should be taken into consideration when investigating the influence of the translation process on the translated language.